Results of Iliac Branch Devices in Octogenarians Within the pELVIS Registry. (February 2021) - Fargion, Aaron Thomas; Masciello, Fabrizio; Pratesi, Giovanni; Torsello, Giovanni; Donas, Konstantinos P.; Pratesi, Carlo
Purpose: To evaluate if the elderly could benefit from the implantation of iliac branch devices (IBDs) to preserve the patency of the internal iliac artery (IIA) in aneurysms involving the iliac bifurcation.Materials and Methods: From January 2005 to April 2017, 804 patients enrolled in the pELVIS registry underwent endovascular aneurysm repair with 910 IBDs due to aneurysmal involvement of the iliac bifurcation. Among the 804 patients, 157 (19.5%) were octogenarians (mean age 82.9±2.5 years; 157 men) with 171 target IIAs for preservation. Outcomes at 30 days included technical success, death, conversion to open surgery, and major complications. Outcomes evaluated in follow-up were patency of the IBD and target vessels, type I and type III endoleaks, aneurysm-related reinterventions, aneurysm-related death, and overall patient survival. Kaplan-Meier analyses were employed to evaluate the late outcome measures; the estimates are presented with the 95% confidence interval (CI).Results: Technical success was 99.4% with no intraoperative conversions or deaths (1 bridging stent could not be implanted, and the IIA was sacrificed). Perioperative mortality was 1.9%. The overall perioperative aneurysm-related complication rate was 8.9% (14/157), with an early reintervention rate of 5.1% (8/157). Median postoperative radiological and clinical follow-up were 21.8 months (range 1–127) and 29.3 months (range 1–127), respectively. Estimated rates of freedom from occlusion of the IBD, the IIA, and the external iliac artery at 60 months were 97.7% (95% CI 96.1% to 99.3%), 97.3% (95% CI 95.7% to 98.9%), and 98.6% (95% CI 97% to 99.9%), respectively. Estimated rates of freedom from type I and type III endoleaks and device migration at 60 months were 90.9% (95% CI 87% to 94.3%), 98.7% (95% CI 97.5% to 99.8%), and 98% (95% CI 96.4% to 99.6%), respectively. Freedom from all cause reintervention at 60 months was 87.4% (95% CI 82.6% to 92.2%). The estimated overall survival rate at 60 months was 59% (95% CI 52.4% to 65.6%).Conclusion: IBD implantation in octogenarians provided acceptable perioperative mortality and morbidity rates, with satisfying long-term freedom from IBD-related complications and should be considered a feasible repair option for selected elderly patients affected by aneurysms involving the iliac bifurcation.